Metabolic syndrome and insulin resistance in patients with vitiligo: A cross-sectional study - Vijaya Ramya Rao; Remya Raj Rajamohanan; Mohamed Salahudeen; Sheela Kuruvila (Wolters Kluwer Medknow Publications, 2023)
Background: Vitiligo is nowadays considered a systemic disease owing to its complex, multifactorial pathogenesis. A possible association of vitiligo with metabolic syndrome as well as insulin resistance has been gaining interest recently. Shared factors in pathogenesis are being proposed as the reason for this interesting association. Aim: We undertook this study to look for the association of vitiligo and its severity with metabolic syndrome and insulin resistance in a South Indian population. Methods: This was a single-center cross-sectional analytical study conducted among patients with vitiligo. Hundred patients with non-segmental vitiligo fulfilling inclusion and exclusion criteria were enrolled in this study after obtaining informed consent. A detailed history was elicited, and a clinical examination was done, including anthropometric measurements and the calculation of the Vitiligo Area Severity Index (VASI). Fasting blood samples were collected to test for blood glucose, lipid profile, serum insulin, and TSH. Insulin resistance was calculated using the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) index, and metabolic syndrome was diagnosed based on revised NCEP-ATP III criteria. Results: Out of the 100 patients with non-segmental vitiligo enrolled in the study, 49 had metabolic syndrome. 31% patients had hyperglycemia, 28% had hypertension, and 28% had hyperlipidemia. Seventy-one patients had low HDL levels, and 74 had a high waist circumference. Fasting insulin levels were found to be higher than normal in 13 patients, while insulin resistance was present in 70 patients. However, there was no significant association between VASI scores and fasting insulin levels (Mann-Whitney U test, P = 0.7), insulin resistance (P = 0.6), or metabolic syndrome (Chi-square test, P = 0.4). Also, there was no significant association between metabolic syndrome and duration of vitiligo (Mann-Whitney U test, P = 0.2) or any clinical type of vitiligo (Chi-square test, P = 0.6). Conclusion: In our study, the prevalence of metabolic syndrome and insulin resistance was found to be significantly higher in vitiligo patients compared to the normal population. However, the presence of the various components of metabolic syndrome or insulin resistance was not associated with the duration or severity of the disease.